Cultivating the conditions for care: it's all about trust - Kooijman, Allison; Canfield, Carolyn (Frontiers in Health Services, 2024)
This perspective article shares the viewpoints of two long-standing patient safety advocates who have participated first-hand in the evolution of patient engagement in healthcare quality and safety. Their involvement is motivated by a rejection of the common cruelty of institutional betrayal that compounds harm when patient safety fails. The advocates have sought to understand how it can be that fractured trust spreads so predictably after harm, just when it most needs strengthening. Instead, the abandonment of trust upends healthcare values and effectiveness at interpersonal, systemic and structural levels. They argue that authentic care (healthcare that is truly caring) transcends mere service delivery, thus embodying an inviolable commitment to mutual well-being, compassion and generosity. The advocates identify the influence of social determinants, such as culture, identity, and socioeconomic status, as critical to trust formation, where pathogenic vulnerability exacerbates existing inequalities and further impedes trust. The advocates call for a shift from transactional to relational, trust-based interactions that explore the potential for mobilizing restorative justice principles to repair harm and rebuild trust, enabling dialogue, mutual understanding and systemic improvement. Trust, they assert, is born in relationships, not transactions. The bureaucratic, legal and resource constraints that often impair meaningful interactions, also cause moral distress to healthcare providers and poor care quality for patients. They argue that central to the current healthcare crisis is the fundamental need for genuine connection and trust, framing this as both a practical necessity and a confirmation of humanity as intrinsic to healthcare. The advocates envision a future where patient engagement is integral to patient safety to prioritize epistemic justice, mutual respect and compassionate care, to restore healthcare as a cohesive, supportive and deeply human endeavor. They query what contributions a restorative approach could make to centre trust as necessary for cultivating the conditions for care in our healthcare system.